Activity of the genus Zanthoxylum against diseases caused by protozoa: A systematic review - Correa-Barbosa, Juliana; Sodré, Daniele Ferreira; Nascimento, Pedro Henrique Costa; Dolabela, Maria Fâni (Frontiers in Pharmacology, 2023)
Neglected diseases (ND) are treated with a reduced variety of drugs, with high cost and toxicity, which makes the search for therapeutic alternatives important. In this context, plants, such as those from the genus Zanthoxylum, can be promising due to active substances in their composition. This study evaluates the potential of species from this genus to treat ND. Initially, a protocol was developed to carry out a systematic review approved by Prospero (CRD42020200438). The databases Pubmed, BVS, Scopus, Science Direct and Web of Science were used with the following keywords: “zanthoxylum”, “xanthoxylums”, “fagaras”, “leishmaniasis”, “chagas disease”, “malaria” and “African trypanosomiasis”. Two independent evaluators analyzed the title and abstract of 166 articles, 122 were excluded due to duplicity or for not meeting the inclusion criteria. From the 44 selected articles, results of in vitro/in vivo tests were extracted. In vitro studies showed that Z. rhoifolium, through the alkaloid nitidine, was active against Plasmodium (IC50 <1µg/mL) and Leishmania (IC50 <8µg/mL), and selective for both (>10 and >30, respectively). For Chagas disease, the promising species (IC50 <2µg/mL) were Z. naranjillo and Z. minutiflorum, and for sleeping sickness the species Z. zanthoxyloides (IC50 <4µg/mL) stood out. In the in vivo analysis, the most promising species were Z. rhoifolium and Z. chiloperone. In summary, the species Z. rhoifolium, Z. naranjillo, Z. minutiflorum, Z. zanthoxyloides and Z. chiloperone are promising sources of active molecules for the treatment of ND.